Pengaruh Laba dan Arus Kas Operasi untuk Memprediksi Kondisi Financial Distress pada Perusahaan Manufaktur SubSektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Rosdiana, Mega; Lasmini, Lilis; Nadeak, Thomas (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This research aims to analyze the influence of operating profits and cash flow in food and beverage companies listed on the Indonesia Stock Exchange during the period 2018 to 2022 in determining financial distress conditions. In this research, the Return On Asset indicators and operating cash flow ratio were used, as well as quantitative-based research methods. The sample consists of 100 data covering 20 food and beverage subsector companies from 2018 to 2022, selected using a purposive sampling technique. The statistical analysis applied involves multiple linear regression, classical assumption testing, descriptive statistical analysis, correlation analysis, determination analysis, and hypothesis testing. The research results show that profit has a significant influence on financial distress, as well as operating cash flow. Simultaneously, operating profit and cash flow have an impact on changes in financial distress.